Determination of microbiological, chemical, and sensory characteristics of hosmerim desserts derived from sheep, goat, and cow cheese - Yılmaz Seçim; Gürkan Uçar (Eurasian Journal of Veterinary Sciences)
Aim: It is aimed to determine the quality characteristics of the hosmerim desserts produced by using goat, sheep and cow cheeses during storage. Materials and Methods: The cheeses have been produced from goat, sheep and cow milk obtained from farms producing under controlled conditions. The three groups production of the hosmerim was carried out in 3 replicates. Analyzes of microbiological, chemical, physicochemical and sensory properties were made and statistical analyzes were made on days 7 and 14 after the production of the Hosmerim desserts. Results: There were no differences in dry matter, ash and acidity values (p> 0,05) of Hosmerim desserts. It was determined that there were significant differences (p <0.01, p <0.001) at 7th and 14th days when the pH values of the hosmerim samples could not be determined at 0 day (p> 0,05). There were differences in the fat, color, textural and sensory analysis values of the samples at days of storage 0,7 and 14. No microorganisms were found in Hosmerim desserts. Conclusion: It has been observed that Höşmerim desserts produced using standard method and packaged with apropriate materials can be microbiologically and chemically preserved for 14 days and sensory properties maintenance for 7 days after production under standard conditions and packaging with appropriate materials. It is thought that which milk is used in the production of cheese used in the production of cheese dessert should be stated in a certain way.